2023
DOI: 10.3390/curroncol30030220
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a Textbook Outcome in Colon Cancer Surgery Is Associated with Improved Long-Term Survival

Abstract: Background: Colon cancer surgery is a complex clinical pathway and traditional quality metrics may exhibit significant variability between hospitals and healthcare providers. The Textbook Outcome (TO) is a composite quality marker capturing the fraction of patients, in whom all desired short-term outcomes of care are realised. The aim of the present study was to assess the TO in a series of non-metastatic colon cancer patients treated with curative intent, with emphasis on long-term survival. Methods: Stage I–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The main characteristics of the included studies are shown in Table 1[6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Twelve studies (70.6%) have been published in the last 3 years and 94.1% in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 1[6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Twelve studies (70.6%) have been published in the last 3 years and 94.1% in the last 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…For colorectal cancers, previous authors have commented on the utility of TOO as a composite metric associated with increased survival when achieved, while few prior studies have examined TOO in patients undergoing surgical resection for colorectal liver metastasis. 4,7,27 To our knowledge, however, no study has sought to understand how safety-net hospital burden affects the achievement of TOO and subsequent long-term survival. In addition, our study establishes that the TOO paradigm can be applied to colorectal cancer with metastasis to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…While clinicians will aim for perfection in their work, quality metrics met by fewer than half of patients warrant reevaluation of patient, tumor, facility, and provider‐specific factors. For colorectal cancers, previous authors have commented on the utility of TOO as a composite metric associated with increased survival when achieved, while few prior studies have examined TOO in patients undergoing surgical resection for colorectal liver metastasis 4,7,27 . To our knowledge, however, no study has sought to understand how safety‐net hospital burden affects the achievement of TOO and subsequent long‐term survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations